Character Education-Oriented E-Module to Improve Learning Independence in Fourth-Grade Social Studies - Nadia Arbreka Br S Pandia; I Gede Astawan; Ni Ketut Desia Tristiantari (Indonesian Values and Character Education Journal, 2025)
The low level of students’ learning independence in Social Studies indicates the suboptimal integration of character values in the learning process and the limited availability of teaching materials that support independent learning. This study aims to develop and examine the effectiveness of a character oriented e-module in improving elementary school students’ learning independence. This research employed a research and development approach using the ADDIE model (analysis, design, development, implementation, and evaluation). The subjects of the study consisted of 34 fourth grade students. Data were collected through validation questionnaires completed by material and media experts, student response questionnaires, and a learning independence test instrument. Data analysis was conducted using descriptive quantitative and qualitative techniques as well as inferential statistical tests to determine the effectiveness of the developed product. The results showed that the developed e-module met the criteria of being highly feasible based on expert validation, received positive responses from students, and was significantly effective in enhancing learning independence. Thus, the product supports more structured learning and strengthens students’ character development. The findings imply that the integration of character education into digital teaching materials should be systematically implemented to improve the quality of learning processes and outcomes.